Family support during childhood as a predictor of mate retention and kin care in adults during the COVID-19 pandemic in Brazil: an exploratory study - Tasso, Natália de Araújo Miranda; Castro, Felipe Nalon (Frontiers in Psychology, 2023)
Introduction Experiences during development help to explain behavior expression in adulthood. Aims In this study, we explored how unpredictability and harshness experienced during childhood may have impacted the occurrence of reproductive milestones in adulthood and the expression of fundamental motives related to self-protection, disease avoidance, mate seeking, mate retention, and kin care (children/family) during the pandemic. Methods This was an exploratory study with 438 participants. Through the administration of online questionnaires, participants were assessed and categorized based on their childhood experiences, resulting in three groups: low unpredictability, high unpredictability with family support, and high unpredictability without family support. Results We found that family support experienced during childhood predicts a slow life-history strategy. This involves an emphasis on growth and parenting efforts at the expense reproduction and was relevant even for participants who faced financial unpredictability. During the pandemic, we also observed that mate retention and kin care (family) motives were predominant among individuals who had greater family support during childhood. Discussion Overall, the findings suggest that unpredictability experienced during childhood is crucial for the development of life-history strategies and the manifestation of fundamental motives in adulthood.